PEMBERDAYAAN DIFABEL MELALUI USAHA EKONOMI PRODUKTIF (UEP) DI DESA KEDIRI, KECAMATAN KEDIRI, KABUPATEN LOMBOK BARAT NUSA TENGGARA BARAT - Siti Aesah; Yhonanda Harsono; Derizka Inva Jaswita (Derivatif : Jurnal Manajemen, 2020)
Empowerment is one of the development strategies for enhancing creativity, especially for people with disabilities who are given knowledge and skills training to live independently. This study aims to determine the form of empowerment that is conducted on the disabled people, especially for people with disabilities in Kediri village, Kediri sub-district of West Lombok Regency through the Productive Economic Enterprises (UEP) program as well as identifying supporting and inhibiting factors. This research is using the qualitative descriptive method. The technique of data collection by interview, observation, and literature study. The research results showed that the empowerment of people with disabilities in Kediri village, Kediri sub-district of West Lombok Regency has not been maximized but good enough because there are still expectations of the disables that have not been fulfilled. People with disabilities want to be given continuous education and training programs related to the Productive Economic Enterprises program because the major factor for the success of the UEP program is Human Resource Development in advance.Keywords: Empowerment, Diffable, Productive Economic Enterprises